Under the dome : a novel - King, Stephen, 1947- (New York : Scribner, 2009)
The small town of Chester's Mill, Maine, is faced with a big dilemma when it is mysteriously sealed off by an invisible and completely impenetrable force field. With cars and airplanes exploding on contact, the force field has completely isolated the townspeople from the outside world. Now, Iraq war vet Dale Barbara and a group of the town's more sensible citizens must overcome the tyrannical rule of Big Jim Rennie, a politician bent on controlling everything within the Dome.
Keywords: Maine -- Fiction; Psychological fiction; Suspense fiction